More DCCA-secure public-key encryptions from KEM + DEM style hybrid paradigms and some observations on the 'inner-outer' structure. (1st January 2014) - Chen, Yuan; Chen, Xiaofeng; Li, Hui
Detectable Chosen Ciphertext Security (DCCA security) is a weaker notion than CCA security. An 'inner-outer' structure is shown to build a CCA-secure PKE from a DCCA-secure PKE, a 1-bounded CCA-secure PKE, and a CPA-secure PKE. In this paper, we first show passive security for DEMs is sufficient for achieving DCCA-secure hybrid PKEs both for KEM+DEM and Tag-KEM/DEM paradigms. Then two DCCA-secure PKEs constructed from CCA secure KEMs are presented. In addition, a counter example to show that the 1-bounded CCA secure component in the 'inner-outer' structure cannot be weakened to CPA one is given, and some possible methods for constructing CCA-secure PKEs from DCCA-secure KEMs are discussed.